High-efficiency oligonucleotide-directed plasmid mutagenesis. - Olsen, D B (1990)
A number of single- and double-base substitutions have been introduced into either the polylinker region or the lacZ gene in the plasmid vector pUC19. The efficiencies of these changes upon transfection of TG-1 bacterial cells were generally 70-80%. A strategy has been devised by which the wild-type DNA can be selectively destroyed. It is primarily based on the resistance of phosphorothioate internucleotide linkages to some restriction enzymes. A mismatch oligonucleotide is introduced into a gapped region and the gap is filled using three deoxynucleoside 5'-triphosphates and one deoxynucleoside 5'-[alpha-thio]triphosphate. Reaction with a restriction enzyme that is unable to hydrolyze phosphorothioates ensures that the DNA containing the mismatch oligonucleotide is only nicked. Concomitantly, the DNA that does not contain the desired mutation is linearized. Subsequent reactions with an exonuclease and DNA polymerase I yield mutant homoduplex DNA for transfection.